Edukasi interaktif kesehatan bayi dan balita sebagai pencegahan stunting melalui program belajar lapangan di Desa Burai - Najmah, Najmah; Maharani, Azzahra; Abdillah, Muhammad Yusuf; Nengsih, Nengsih; Miyarti, Sinta (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Stunting is a nutritional problem in toddlers and is still a public health problem in developing countries like Indonesia. Currently, Indonesia is still the country with the highest prevalence of stunting among countries in Southeast Asia. Ogan Ilir Regency is the area with the second largest prevalence of stunting in South Sumatra, which will affect the development performance of the area, whether related to economic growth, poverty or inequality. The aim of this community service activity is to provide education to mothers who have babies or toddlers about stunting and how to prevent it in Burai Village. By holding this activity, it is hoped that mothers who have babies/toddlers will know, be willing and able to achieve healthy babies/toddlers with good nutritional status and growth and development. This service activity takes the form of implementing stunting and MPASI educational activities starting with anthropometric measurements of babies/toddlers, counseling about stunting and what's on my plate, providing material about MPASI and closing with a question and answer session. Interactive Educational Activities on Baby/Toddler Health as Prevention of Stunting is one part of the implementation of Field Learning Experiences (PBL) in Burai Village which is expected to increase awareness and knowledge of pregnant women or mothers who have babies/toddlers in preventing stunting as well as providing good complementary foods. adjusted according to age.